Sistem Informasi Akuntansi Peternakan Ayam Petelur PT. GUJ - Kristiardy Hansel Guntoro; Silvia Rostianingsih; Christian Purnama (Jurnal Infra, 2017)
Laying Chicken Farm PT. GUJ, currently still using the system for recording purchases, chicken cultivation, egg production, and sales manually. This resulted in difficulty to know the cost of good sold of the egg quickly and also analyze the effect of certain food consumption to certain chickens of Laying Chicken Farm PT. GUJ.Because of the problems faced by the Laying Chicken Farm PT. GUJ, application is made to help solve the existing problems in the Laying Chicken Farm PT. GUJ. This application includes a computerized system of purchase, chicken cultivation, egg production, sales, profit and loss calculations, balance sheet, and display the necessary reports farm. This application uses the programming language Laravel Framework and MySQL.Based on the results of tests performed, 80% of users stated that the features in this application is sufficient to help overcome the existing problems on the farm.